Explorando los cambios de la pobreza en Argentina: 2003-2015 - Jessica Bracco; Leonardo Gasparini; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
– This paper explores the changes in income poverty in Argentina during the period 2003-2015 using various decomposition methodologies. The results suggest that the generalized improvement in the labor market after the crisis was the main factor behind the sharp fall in poverty in the period 2003-2007. In contrast, the reduction of poverty between 2007 and 2011 is associated with the most active role played by social policy. Finally, during the period 2011-2015, no factor could contribute significantly to the reduction of poverty.
Keywords: C15; D31; D33; I32; J31; 330